2018
DOI: 10.1111/exd.13744
|View full text |Cite
|
Sign up to set email alerts
|

Murine type VII collagen distorts outcome in human skin graft mouse model for dystrophic epidermolysis bullosa

Abstract: Human skin graft mouse models are widely used to investigate and develop therapeutic strategies for the severe generalized form of recessive dystrophic epidermolysis bullosa (RDEB), which is caused by biallelic null mutations in COL7A1 and the complete absence of type VII collagen (C7). Most therapeutic approaches are focused on reintroducing C7. Therefore, C7 and anchoring fibrils are widely used as readouts in therapeutic research with skin graft models. In this study, we investigated the expression pattern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
0
10
1
Order By: Relevance
“…We confirmed that this antibody is human specific by immunohistochemistry with control sections of RDEB patient skin, normal human skin, and mouse skin. In contrast to the previous report by Bremer et al 25 , murine COL7 was not detected in our study in grafts of ESS containing RDEB fibroblasts and keratinocytes at 1 to 3 weeks after grafting. This may be due to differences in the models used in the two studies.…”
Section: Discussioncontrasting
confidence: 99%
“…We confirmed that this antibody is human specific by immunohistochemistry with control sections of RDEB patient skin, normal human skin, and mouse skin. In contrast to the previous report by Bremer et al 25 , murine COL7 was not detected in our study in grafts of ESS containing RDEB fibroblasts and keratinocytes at 1 to 3 weeks after grafting. This may be due to differences in the models used in the two studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Complementary to genetic mouse models, studies on topical curative therapies, but also other lines of therapies, have frequently used grafting of human skin equivalents or similar onto immunodeficient mice [ [16] , [17] , [18] ]. Nevertheless, the evaluation of collagen VII abundance and deposition in the grafts can be influenced by collagen VII expressed by the wild-type host [ 19 ]. In this context – and for all other preclinical studies introducing human collagen VII in murine hosts – tools to specifically detect human and murine collagen VII would be valuable.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have shown that the mouse monoclonal collagen VII antibody LH 7: 2 [ 20 , 21 ], which is widely used for diagnostics to detect human collagen VII, recognizes human but not murine collagen VII [ 12 , 19 ]. However, commonly used hosts for human skin and cell grafting such as SCID or athymic nude mice [ [16] , [17] , [18] ] are leaky or maintain production of immunoglobulins which distorts staining with mouse monoclonal antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Turczynski et al showed that ∆73 collagen VII is capable of forming anchoring fibrils in vivo (Turczynski et al 2016) suggesting that even if flexibility is reduced, anchoring fibril formation is still possible. However, these studies were performed in collagen VII-competent mice contribution and host-synthesized collagen VII could thus have influenced the results (Bremer et al 2019b). QR-313-induced collagen VII expression promoted skin stability in exon73-mutated RDEB and DDEB HSEs.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%